Serbian Translation of French Code of Civil Procedure from 1837. Part two: legal terminology of theTranslation - Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The article deals with legal terms appearing in Serbian translation of French Code of Civil Procedure (Code de procédure civile, 1806) authored by Serbian writer and politician Lazar Zuban (1795–1850). The author made an attempt to determine whether the terms used by Zuban had existed in historical sources previous to the translator’s work. If so, it would mean that Zuban was using already existing technical terms. In cases in which he failed to find certain legal term in texts older than Zuban’s work, the author tried to establish if the unfound term had been the translator’s invention. As to the terms of civil law, Zuban mostly took over words already present in Serbian vocabulary at the time. Тhis fact is easily explainable: family, property, contracts, torts, inheritage are very present in people’s everyday life, which brought about terminology of civil law to be relatively developed. On the contrary, terms belonging to the civil procedure were scarce because judiciary and court procedure in the time of Zuban’s work were still being on rudimentary level. That is the reason why the translator had to forge his own legal terms. Zuban did not translate German legal terms (the translator used German translation of a Code as protograph) mechanically; he was making effort to fathom the meaning of a word in question and find its adequate Serbian equivalent. In some cases that effort was fruitful. Nevertheless, in a long term Zuban’s labor was in vain, as none of his forged words survived in Serbian legal terminology.